Modulação do sistema endocanabinoide sobre respostas neuroinflamatórias em modelo animal de encefalite causada pelo vírus Herpes simplex tipo 1 - Viviane Mitsuko Neves Saito (2011)
The Herpes simplex virus type 1 (HSV-1) is a pathogen known to cause recurrent skin lesions and to establish a latent state between manifestations. However, the most serious consequence of HSV-1 infection is herpes encephalitis (HSE), affecting mainly immunocompromised patients and neonates. Once the infection reaches the cerebral tissue, several inflammatory mechanisms are triggered to defend the host against the virus. The aim of this research was to investigate the modulatory role of the cannabinoid agonist WIN55,212-2 on the development of inflammatory and behavioral changes in mice with HSE. Male C57BL/6 mice, aged 8 to 12 weeks, were used in this study. These animals were intracranially inoculated with 102 plaque forming units (PFU) of HSV-1, while the uninfected control group received only PBS by the same route. Mice were also treated with WIN55,212-2 (1 mg/kg) or vehicle intraperitoneally (i.p), and the treatment started the day before infection and continued until euthanasia. In the first stage of the project, we used untreated infected mice (HSV+VEH) and treated infected mice (HSV + WIN) to build a lethality curve and to assess the onset of clinical signs, for 10 days post infection (10 dpi) using the SHIRPA battery. Thereafter, another data set was obtained on the 4 dpi, regarding the brain levels of cytokines and histopathology of the hippocampus. For this we used four experimental groups (uninfected untreated mice - CTRL + VEH; uninfected treated mice - CTRL + WIN; untreated infected mice - HSV + VEH, and infected treated mice - HSV + WIN). At last, we assessed specific behavioral changes in animal models of anxiety and memory, i.e, Inhibitory Avoidance paradigm, the Elevated Plus Maze and Social Recognition Test, all held between 1 and 2 dpi. Three groups had their results compared (CTRL+VEH, HSV+VEH and HSV+WIN). Animals from this experiment were euthanized on 3 dpi for microscopic analysis of neuronal loss in the hippocampus. Surprisingly, the results indicate that clinical signs (such as marked loss of body weight, changes in reflexes, sensory function and lowering in the neuropsychiatric status) first appeared in HSV+WIN mice and then in HSV+VEH animals. The survival rate of HSV+WIN mice was also lower (100% mortality on 6 dpi) compared to HSV+VEH group (100% mortality on 10 dpi). Short-term social memory was also impaired in HSV+WIN mice, whereas HSV+VEH mice showed only mild damage. However, no differences were found between groups concerning the acquisition, consolidation and retrieval of aversive memory in the Inhibitory Avoidance paradigm. In the EPM, HSV+VEH mice exhibited lower rates of anxiety-like behavior than HSV+WIN animals. The levels of IL-1 and TNF- were increased in infected mice, regardless of treatment. Data from histopathological analysis and quantification of neuronal death in the hippocampus also did not differ significantly between HSV+VEH and HSV+WIN groups. Therefore, it is concluded that treatment with the cannabinoid agonist WIN55,212-2 had a deleterious effect on the course of HSE in C57BL/6 mice, accelerating mortality and promoting more prominent symptoms of the disease, although it did not directly influenced the levels of cytokines or cellular/tissue loss in mice brain.